Trichothecenes: immunomodulatory effects, mechanisms, and anti-cancer potential - Wu, Qinghua; Wang, Xu; Nepovimova, Eugenie; Miron, Anca; Liu, Qianying; Wang, Yun; Su, Dongxiao; Yang, Hualin; Li, Li; Kuca, Kamil (Archives of toxicology, 2017)
Paradoxically, trichothecenes have both immunosuppressive and immunostimulatory effects. The underlying mechanisms have not been fully explored. Early studies show that dose, exposure timing, and the time at which immune function is assessed influence whether trichothecenes act in an immunosuppressive or immunostimulatory fashion. Recent studies suggest that the immunomodulatory function of trichothecenes is also actively shaped by competing cell-survival and death-signaling pathways. Autophagy may also promote trichothecene immunosuppression, although the mechanism may be complicated. Moreover, trichothecenes may generate an "immune evasion" milieu that allows pathogens to escape host and vaccine immune defenses. Some trichothecenes, especially macrocyclic trichothecenes, also potently kill cancer cells. T-2 toxin conjugated with anti-cancer monoclonal antibodies significantly suppresses the growth of thymoma EL-4 cells and colon cancer cells. The type B trichothecene diacetoxyscirpenol specifically inhibits the tumor-promoting factor HIF-1 in cancer cells under hypoxic conditions. Trichothecin markedly inhibits the growth of multiple cancer cells with constitutively activated NF-κB. The type D macrocyclic toxin Verrucarin A is also a promising therapeutic candidate for leukemia, breast cancer, prostate cancer, and pancreatic cancer. The anti-cancer activities of trichothecenes have not been comprehensively summarized. Here, we first summarize the data on the immunomodulatory effects of trichothecenes and discuss recent studies that shed light on the underlying cellular and molecular mechanisms. These mechanisms include autophagy and major signaling pathways and their crosstalk. Second, the anti-cancer potential of trichothecenes and the underlying mechanisms will be discussed. We hope that this review will show how trichothecene bioactivities can be exploited to generate therapies against pathogens and cancer.
Keywords: signální transdukce; Signal Transduction; Humans; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Signaling pathway; Trichothecenes; lidé; trichotheceny; autofagie; Immunoglobulin A; infekce; imunosupresiva; Deoxynivalenol; Anticarcinogenic Agents; Anti-cancer; Immunosuppressive Agents; imunologické faktory; Immune evasion; antikarcinogenní látky; T-2 toxin; Immunologic Factors; imunoglobulin A; Immunomodulation; Autophagy; Infections